Factors Influence Financial Inclusion: Evidence from Indonesian Micro Data - Etty Susilowati; L. Leonnard (Faculty of Economic and Business, 2019)
In order to increase access to formal financial institutions, the Indonesian government has issued various national strategies. However, Indonesia’s inclusive financial index is still under other ASEAN countries. Therefore, in this study, we investigate the factors that influence financial inclusion in Indonesia. The microdata from global findex 2014 was carried out in this study by using binary logistic regression analysis. The finding indicates that there is a significant positive relationship between individual characteristics, including financial inclusion, constraints to financial inclusion, utilization of financial services motivation, and loan sources. Since the main targets of financial inclusion are the poor, this finding becomes an essential proposition for policies in the banking sector, that besides the factors of gender, age, education, and type of jobs, income is the primary factor that influences access and utilization of financial services. Mainly regarding loans, increased income will increase the opportunities of the poor to getting loans because only high-income groups have collateral in applying for loans.JEL Classification: D14, G20